EFFICACY AND SAFETY OF AFLIBERCEPT FOR THE TREATMENT OF IDIOPATHIC CHOROIDAL NEOVASCULARIZATION IN YOUNG PATIENTS: The INTUITION Study. Issue 2 (February 2022) - Kodjikian, Laurent; Tadayoni, Ramin; Souied, Eric H.; Baillif, Stéphanie; Milazzo, Solange; Dumas, Stéphane; Uzzan, Joël; Bernard, Lorraine; Decullier, Evelyne; Huot, Laure; Mathis, Thibaud
Abstract : Purpose: To evaluate the mean change in visual acuity at 52 weeks in patients with idiopathic choroidal neovascularization treated with aflibercept. Methods: We conducted a prospective noncomparative open-label Phase-II trial. The dosage regimen evaluated in this study was structured into two periods: (1) from inclusion to 20 weeks: a treat-and-extend period composed of three mandatory intravitreal injections, and complementary intravitreal injections performed if needed; (2) from 21 weeks to 52 weeks: a pro re nata period composed of intravitreal injections performed only if needed. Results: A total of 19 patients were included, and 16 completed the 52-week study. At baseline, the mean best corrected visual acuity was 66.56 (±20.72) letters (≈20/50 Snellen equivalent), and the mean central retinal thickness was 376.74 µ m (±93.77). At 52 weeks, the mean change in the best-corrected visual acuity was +19.50 (±19.36) letters [95% confidence interval = +9.18 to +29.82]. None of the patients included lost ≥15 letters at 24 weeks or 52 weeks. The mean change in central retinal thickness was −96.78 µ m (±104.29) at 24 weeks and −86.22 µ m (±112.27) at 52 weeks. The mean number of intravitreal injections was 5.4 (±3.0) at 52-weeks. No ocular serious adverse events related to the treatment were reported. Conclusion: The present analysis shows clinically significant functional and anatomical treatment effect of aflibercept in case of idiopathic choroidal neovascularization. The treat-and-extend regimen proposed after the first injection seems adequate to treat most neovessels. Abstract : This prospective noncomparative open-label Phase II trial evaluates patients with idiopathic choroidal neovascularization treated with aflibercept. We found a clinically significant functional and anatomical treatment effect for aflibercept.